CHARACTER-BASED ENGLISH EDUTAINMENT LEARNING USING POWTOON MEDIA FOR FOURTH-GRADE STUDENTS - Made Tantri Pratiwi; Luh Diah Surya Adnyani; G.A.P. Suprianti (Prasi: Jurnal Bahasa, Seni, dan Pengajarannya, 2022)
The latest trend in learning English for elementary school students is the implementation of Edutainment in learning. Edutainment can create a learning atmosphere that is fun, interesting, creative, innovative, and meaningful. One of the edutainment media is character-based PowToon. This study aims to determine the difference in English comprehension between students taught with PowToon media and those taught without PowToon media. This research is a mixed type with a posttest-only control group design. The experimental class was treated with PowToon media, and the control class was taught without using PowToon media. The data required consists of data on learning outcomes and student responses to the learning process. Learning outcomes were collected by written and oral tests, while questionnaires and interviews collected data on student responses. The data obtained were analyzed using SPSS v25.0. The research results show that using PowToon in learning English positively affects students' understanding of English. The characteristics displayed by the experimental class students during the study were nationalist, religious, honest, diligent, disciplined, independent, responsible, and empathetic.